(23)Na MRI reveals persistent sodium accumulation in tumefactive MS lesions - Huhn, Konstantin; Mennecke, Angelika; Linz, Peter; Tschunko, Franz; Kästle, Nicola; Nagel, Armin Michael; Uder, Michael; Dörfler, Arnd; Linker, Ralf; Engelhorn, Tobias (Journal of the Neurological Sciences, 2017)
Chronic inflammatory demyelinating diseases of the CNS typically show a limited lesion size. However, extended lesions may appear with an atypical configuration. Large lesions with a diameter>2cm accompanied by tumor-like edema are entitled "tumefactive" and may occur in multiple sclerosis (MS) and other demyelinating diseases. Historically, differential diagnosis often requires histological analysis. Therefore, advanced imaging techniques are warranted to allow for a precise non-invasive diagnosis. Cerebral sodium ((23)Na) MRI was recently described as a new method to investigate in vivo sodium accumulation. Indicating extended sodium levels in MS lesions, (23)Na MRI is a promising differential diagnostic tool further elucidating the role of sodium in demyelinating lesions.Repetitive (23)Na MRI measurements in a MS patient with a tumefactive demyelinating lesion providing insight into the medium-term course of cerebral sodium levels.(23)Na MRI depicts persistent lesional sodium accumulation after anti-inflammatory treatment and provides the opportunity of a non-invasive, in vivo analysis of sodium levels in inflammatory CNS lesions without need for contrast enhancing media. As a result of the extended dimension, tumefactive lesions may have an appropriate size for the analysis of inflammatory demyelination by (23)Na MRI with sufficient resolution.
EVALuna2:14686

Radiostereometric migration analysis of the Cerafit femoral stem: 28 patients followed for 2 years - Tschunko, Franz; Wagner, Benedikt; Hong, Yutong; Söder, Stephan; Wölfel, Rainer; Müller, Lutz Arne; Forst, Raimund; Sesselmann, Stefan (Biomedizinische Technik, 2015)
Radiostereometric analysis (RSA) is the gold standard evaluating micromovements after total hip arthroplasty. The aim of this study was to investigate the migratory pattern of an uncemented femoral stem during the first 2 years after surgery. We followed 28 patients with a mean age of 57 (SD 13) years for the first two postoperative years. Radiostereometric analysis was used to measure the translation and rotation of the femoral component. The Harris hip score (HHS) was determined to evaluate the clinical outcome. No stem had to be revised. The mean HHS advanced from 35 (SD 11) preoperative to 89 (SD 10) 1 year after surgery. At the end of the observation period, mean subsidence of the stem was 0.26 mm (SD 0.82). Maximum total point motion (MTPM) was 1.23 mm (SD 1.22). The main distal migration took place up to 6 weeks after surgery with nearly no further subsidence up to 2 years postoperatively. All the measured migrations of the hip stem were very small. Results of the HHS demonstrate good clinical outcome. Long-term RSA is necessary to assess possible late migration of the Cerafit standard femoral stem.
EVALuna2:10856

Radiostereometric migration measurement of an uncemented Cerafit® femoral stem: 26 patients followed for 10 years - Sesselmann, Stefan; Hong, Yutong; Schlemmer, Frank; Hussnaetter, Isabell; Müller, Lutz Arne; Forst, Raimund; Tschunko, Franz (Biomedizinische Technik, 2017)
Radiostereometric analysis (RSA) is the gold standard for evaluating micromotions of orthopaedic implants. The method is applied for identifying novel design weaknesses in endoprostheses. Current research frequently assesses relatively short time periods. Short-term RSA studies have been widely used for predicting the long-term stability of many hip prosthetic designs, but only a few studies have focused on uncemented hip implants, especially for extended periods. The purpose of this study was to analyse the migration pattern of the Cerafit® femoral stem within 10 years and to verify the predictive value of short-term RSA after 2 years for this uncemented femoral hip stem. Twenty-six patients were followed for 10 years. Ten years after implantation, a mean subsidence of 0.22 mm±0.56 mm, a mean internal rotation of 0.59°±1.67° and a mean maximum total point motion (MTPM) of 1.28 mm±0.54 mm were detected. The main migration took place in the first 6 weeks after surgery (subsidence of 0.36 mm±0.73 mm; internal rotation of 0.62°±1.49°, MTPM of 1.05 mm±0.68 mm). All the migration values measured were small. No late-onset migration was observed. This study suggests that the Cerafit® implants are stable after 10 years. Thus, RSA could be the best tool to assess long-term implant behaviour.
EVALuna2:33711